Geopolymers as solid adsorbent for CO2 capture. (12th July 2016) - Minelli, Matteo; Medri, Valentina; Papa, Elettra; Miccio, Francesco; Landi, Elena; Doghieri, Ferruccio
Abstract: Geopolymer materials, a new class of alkali-bonded ceramics, have been prepared in monolith porous form, in order to investigate the adsorptive performances of CO2 and light gases (CH4 and N2 ) by means of a volumetric method in the sub-atmospheric pressure range. The samples have been produced by reacting an aluminosilicate powder with an aqueous alkali silicate solution, in different dilution proportions, achieving very high geopolymerization conversion (higher than 97%). The monoliths microstructural and textural properties have been first characterized by SEM and porosimetric measurements, which revealed the structure of the geopolymer as mainly consisting of nanoprecipitates and mesopores, with overall porosity from 30% up to 60%, and BET surface area up to 50 m 2 /g. The analysis of the gas adsorption properties showed a quite good capacity for CO2 in the geopolymer monoliths, remarkably higher than those of CH4 and N2, pointing out the significant ability in the selective capture of CO2 of these geopolymers. The values of selectivity in capacity obtained from the adsorption measurements, up to 200 and 100 for CO2 /N2 and CO2 /CH4 separation, respectively, are considerably higher than those of most of the adsorbent materials commonly accounted for in such applications. Graphical abstract: Highlights: Alkali-bonded porous monoliths (geopolymers) are prepared and characterized. The CO2 and light gas adsorption capacity of the geopolymer monoliths is analyzed. Measurements revealed a quite good CO2 adsorption capacity. Measurements revealed an excellent CO2 /N2 and CO2 /CH4 capacity selectivity.